Transcriptome and metabolome analyses reveal transcription factors regulating ganoderic acid biosynthesis in Ganoderma lucidum development - Meng, Li; Zhou, Ruyue; Lin, Jialong; Zang, Xizhe; Wang, Qingji; Wang, Panmeng; Wang, Li; Li, Zhuang; Wang, Wei (Frontiers in Microbiology, 2022)
Ganoderma lucidum is an important medicinal fungus in Asian countries. Ganoderic acid is the major variety of bioactive and medicative components in G. lucidum. Biosynthesis of secondary metabolites is usually associated with cell differentiation and development. However, the mechanism underlying these phenomena remain unclear. Transcription factors play an essential regulatory role in the signal transduction pathway, owing to the fact that they represent the major link between signal transduction and expression of target genes. In the present study, we performed transcriptome and metabolome analyses to identify transcription factors involved in ganoderic acid biosynthesis during development of G. lucidum. Transcriptome data revealed differentially expressed genes between mycelia and primordia, as well as between primordia and the fruiting body. Results from gene ontology enrichment analysis and metabolome analyses suggested that ganoderic acids and flavonoids biosynthetic process significantly changed during fungal development. Notably, genes encoding homeobox transcription factor and velvet family protein were significantly enriched in ganoderic acid biosynthesis. Collectively, these results are expected to enhance our understanding into the mechanisms underlying secondary metabolite biosynthesis and development in fungi.